A Micro-assessment of Coronavirus Disease 2019 Realities on Small-Scale Vendors in Ghana: China as a Leveraging Resource. Issue 1 (January 2023) - Ameyaw-Brobbey, Thomas; Amable, Dennis Senam
Since the Coronavirus Disease 2019 (COVID-19) outbreak, international relations (IR) literature on the pandemic's implication on global politics has generally increased, while studies on small businesses and human developmental consequences in the developing world have lagged. In this context, through a micro-level analysis, this article investigates the extent to which the COVID-19 pandemic affects the economically bottom-class citizens and their businesses, focusing on small-scale vendors in Ghana. It utilises content analysis to examine 384 small-scale vendors in four cities/towns (Accra, Tema, Sunyani, Ho) in Ghana between August and October 2021. We show that the pandemic has negatively affected economic life and ordinary living conditions by increasing poverty among economically bottom-class citizens, likely to have dire long-term consequences nationally. Further, we contend that the small-scale vendors and entrepreneurs recognise leveraging the increasing Chinese global economic influence. Thus, China provides an exit point through which the people can navigate themselves out of the COVID-19 predicaments. Our study is novel for its first-level—individual—analysis of the impact of COVID-19 in the Ghanaian market space from an IR perspective. It also provides policy relevance.